Evaluasi Pertumbuhan dan Produksi serta Seleksi Tanaman Jagung Generasi F1-F2 Hasil Persilangan Jagung Pop-Corn dengan Jagung Ungu - Halimi, E. S.; Puteri, E. D.; Adriansyah, F.; Atmi, E. M. (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2024)
Halimi, E. S., Puteri, E. D., Adriansyah, F., & Atmi, E. M. (2024). Evaluation on growth production and selection of corn plants generation F1-F2 from the cross of pop-corn and purple-corn. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-12 Tahun 2024, Palembang 21 Oktober 2024. (pp. 335–343). Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Pop-corn is one of the popular agricultural products as a snack ingredient. Most of the varieties are yellow, white, and not as a purple corn. The research objectives was to determine the growth, production of F1 maize plants and segregation, as well as to produce F2 generation seeds from the crossing of “Orange Featured”, “King Pop” and “Yellow Featured” variety. The research began with a cross between 3 pop-corn accessions as female elders and purple maize as male elders. In this research, the resulted for that cross were planted in a Randomized Block Design. Result of this research indicated that F1-plants generation were capable to grow and produce pop-corn and several cobs with purple F2-seeds for next research. Average plant height at 63-days reached 150.16-179.86 cm, with ear position at 79.93-95.36 cm. Male and female flower anthesis were at 45 and 54 days. The plant height of JPUU-II accession of 150.16 cm was the lowest as compare to others. Observation on production variables resulted these three accessions had about similar dry-weight, number of seed, and weight of 100-seeds, each 67.56-73.63 g/cob, 308-314 seeds/cob and 24.16- 25.63 g/100-seeds. The results of this research showed that F1 generation plants resulting from crossing 3 accessions with purple corn can grow and produce well. The variety “Yelllow seed” has the potential to be a higher-yielding purple corn. Purple color, especially leaf bone color, is used as a variable in the purple maize selection program, because it corresponds to the color of the seeds produced.